An exploration of the optimum dosage and number of cycles of itraconazole pulse therapy for severe onychomycosis. Issue 10 (5th July 2018) - Zhang, Li; Xu, Hui; Shi, Yuling; Yu, Jing; Tao, Yunjiao; Li, Xiuli
Summary: Although standard itraconazole pulse therapy is a well‐established regimen for toenail onychomycosis, the cure rate for onychomycosis remains low. To evaluate the efficacy and safety of different cycles of itraconazole pulse therapy, determine the optimal dosage and number of cycles for onychomycosis. A total of 90 outpatients of our hospital with onychomycosis were randomised into three treatment groups: (1) standard itraconazole pulse therapy (200 mg twice per day, 1 week each month for three pulses); (2) long‐term pulse therapy (200 mg twice per day, 1 week each month for six pulses); (3) low‐dose and long‐term pulse therapy (200 mg/d, 1 week per month for six pulses) and were followed up for 15 months. Of the initial patients, the trial was completed by 81 patients. The complete cure rates were 32.43% for three cycles and 75% for six cycles ( P  < .001). For six cycles, despite the administration of half‐dose for patients weighing no more than 55 kg, there was no statistical difference in the complete cure rate ( P  = .862). Long‐term therapy is effective and safe for the treatment of toenail onychomycosis. For patients weighing no more than 55 kg, long‐term half‐dose itraconazole pulse therapy is recommended .